Evaluating Marketing Communication Strategies within the Digital Economy: A Case Study of Sellen Flowers - Rizki, Achmad; Salas, Hagi Julio; Marini, Marini (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to evaluate marketing communication strategies within the digital economy through a case study of Sellen Flowers, a flower-selling business located in Kotabumi, North Lampung. The research provides insights into effective marketing communication approaches in the digital era, focusing on the use of digital media platforms. A qualitative descriptive method was employed, with data collected through observation, interviews, and document analysis. The primary informant was the owner of Sellen Flowers. Findings reveal that Sellen Flowers primarily utilizes TikTok as their digital marketing platform to showcase flower images and videos, display prices, and promote products. Social media proves to be an effective marketing tool due to its ability to overcome constraints of distance, time, and location. Additionally, Sellen Flowers collaborates with third parties to create mutual benefits. Despite its effectiveness, there remain areas for improvement, such as engaging influencers, expanding partnerships, and enhancing content quality on marketplaces. This study demonstrates that digital marketing can be a successful strategy for increasing sales and reaching a broader customer base in the digital economy. However, it is crucial for businesses to select appropriate platforms, create engaging and informative content, and continuously evaluate and refine their marketing communication strategies, including digital marketing efforts.